2006
DOI: 10.5326/0420234
|View full text |Cite
|
Sign up to set email alerts
|

Severe Cholestatic Liver Disease Secondary to Liver Fluke (Platynosomum concinnum) Infection in Three Cats

Abstract: Three middle-aged domestic cats were presented for vomiting, lethargy, anorexia, and jaundice. Complete blood counts, serum biochemical profiles, and abdominal ultrasounds were suggestive of extrahepatic biliary obstruction in all of the cats. Infection with the liver fluke Platynosomum concinnum was confirmed by intraoperative bile cytology in three cases and by histopathology in two cases. All three cats were euthanized in the postoperative period because of complications. These cases illustrate the severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 5 publications
2
38
1
1
Order By: Relevance
“…Gross pathological lesions observed in the livers of infected cats were similar to previous descriptions of lesions in feline platynosomiasis (HANEY et al, 2006;HEADLEY et al, 2012;BASU & CHARLES, 2014;BRAGA et al, 2016). Milder injuries such as jaundice, parasites in the bile duct and gallbladder, and visualization of bile ducts on the hepatic surface were the abnormalities most commonly observed, while bile duct distension was the most remarkable lesion present in 61.1% of livers from infected animals.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Gross pathological lesions observed in the livers of infected cats were similar to previous descriptions of lesions in feline platynosomiasis (HANEY et al, 2006;HEADLEY et al, 2012;BASU & CHARLES, 2014;BRAGA et al, 2016). Milder injuries such as jaundice, parasites in the bile duct and gallbladder, and visualization of bile ducts on the hepatic surface were the abnormalities most commonly observed, while bile duct distension was the most remarkable lesion present in 61.1% of livers from infected animals.…”
Section: Discussionsupporting
confidence: 84%
“…Taylor & Perri (1977) noted extensive fibrous connective tissue in the bile ducts in the chronic stage (6 months after infection or beyond). Herein, we observed that naturally infected stray cats in an endemic region to platynosomiasis did not present severe pathological conditions such as cystic liver disease, severe cholestatic liver disease, cholangitis and cholangiohepatitis, cholangiocarcinoma, mesenteric lymphadenopathy, and hepatomegaly (O'SULLIVAN et al, 1976;HANEY et al, 2006;XAVIER et al, 2007;CARREIRA et al, 2008;ANDRADE et al, 2012;BRAGA et al, 2016). Morover, the intensity of parasitism was not related to the severity of macroscopic or microscopic hepatic injuries.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…89,90,93,95 Although trauma-related (diaphragmatic herniation) or other extrabiliary causes (duodenal foreign body) of EHBTO are rare, they have been reported, and if addressed in a timely fashion may lead to successful outcomes for the patient. 94,96 Recently a case series of six cats presented data on obstructive sphincter of Oddi Treatment of cholecystitis also depends on the stage of the disease and the clinical picture of the patient.…”
Section: Lobectomy and Hepatectomymentioning
confidence: 97%